Electrochemical Characterization of Modified Glassy Carbon Electrodes for Non-Enzymatic Glucose Sensors - Julia Maria Mazurków; Anna Kusior; Marta Radecka (Sensors, 2021)
The diversity of materials proposed for non-enzymatic glucose detection and the lack of standardized protocols for assessing sensor performance have caused considerable confusion in the field. Therefore, methods for pre-evaluation of working electrodes, which will enable their conscious design, are currently intensively sought. Our approach involved comprehensive morphologic and structural characterization of copper sulfides as well as drop-casted suspensions based on three different polymers—cationic chitosan, anionic Nafion, and nonionic polyvinylpyrrolidone (PVP). For this purpose, scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy were applied. Subsequently, comparative studies of electrochemical properties of bare glassy carbon electrode (GCE), polymer- and copper sulfides/polymer-modified GCEs were performed using electrochemical impedance spectroscopy (EIS) and voltammetry. The results from EIS provided an explanation for the enhanced analytical performance of Cu-PVP/GCE over chitosan- and Nafion-based electrodes. Moreover, it was found that the pH of the electrolyte significantly affects the electrocatalytic behavior of copper sulfides, indicating the importance of OHads in the detection mechanism. Additionally, diffusion was denoted as a limiting step in the irreversible electrooxidation process that occurs in the proposed system.